2019
DOI: 10.1093/gerona/glz107
|View full text |Cite
|
Sign up to set email alerts
|

High Flavonoid Cocoa Supplement Ameliorates Plasma Oxidative Stress and Inflammation Levels While Improving Mobility and Quality of Life in Older Subjects: A Double-Blind Randomized Clinical Trial

Abstract: Background The age-related decline in mass, strength, and performance of skeletal muscle is associated with loss of independence, falls risk, disability, institutionalization, and death. Methods To determine whether a cocoa supplement enriched in flavonoids can improve plasma markers of oxidative stress and inflammation, physical performance and frailty in middle-aged and older subjects, we conducted a two-phase, randomized, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(81 citation statements)
references
References 34 publications
4
77
0
Order By: Relevance
“…In some experiments, extracts rich in bioactive compounds have demonstrated capacity to activate immune cells (Tumova et al, 2017), although with other extracts, no improvement was found (Hunter et al, 2012). On the other hand, high flavonoid cocoa supplements have recently demonstrated their capacity to reduce oxidative stress in plasma and inflammation in older subjects (Munguia et al, 2019). Mediterranean diet, rich in plant foods, is associated with reduced risk of developing age-related chronic diseases by inducing protection against oxidative stress and improving mitochondrial activity that could be the cause of a reduced inflammation level (Tosti et al, 2018).…”
Section: Age-related Immune System Distortion Can Be Prevented By Prolongevity Factorsmentioning
confidence: 99%
“…In some experiments, extracts rich in bioactive compounds have demonstrated capacity to activate immune cells (Tumova et al, 2017), although with other extracts, no improvement was found (Hunter et al, 2012). On the other hand, high flavonoid cocoa supplements have recently demonstrated their capacity to reduce oxidative stress in plasma and inflammation in older subjects (Munguia et al, 2019). Mediterranean diet, rich in plant foods, is associated with reduced risk of developing age-related chronic diseases by inducing protection against oxidative stress and improving mitochondrial activity that could be the cause of a reduced inflammation level (Tosti et al, 2018).…”
Section: Age-related Immune System Distortion Can Be Prevented By Prolongevity Factorsmentioning
confidence: 99%
“…In a similar study in older subjects, functional indicators of frailty such as a 6-minute walk test improved after high avanol cocoa supplementation. Improvements were also accompanied by decreased plasma levels of markers of OS and in ammation (13). In patients with peripheral artery disease, high avanol cocoa supplementation for 3 months led to a signi cant increase in the 6-minute walk test while increasing calf perfusion and capillarity (25) and in Becker muscular dystrophy patients, treatment with Epi (50 mg BID for 2 months) led to increases in quadriceps and plasma follistatin levels while myostatin decreased (14).…”
Section: Discussionmentioning
confidence: 96%
“…In aged mice, Epi restores reactive oxygen species buffering systems and reduces OS in heart and SkM leading to improved function (12). In an aged female rat model of early stage heart failure, Epi signi cantly reduces the plasma levels of multiple cytokines and protein carbonyls an effect, replicated in older human subjects provided high avanol cocoa (13). In a pilot study in patients with Becker muscular dystrophy, multiple serum markers of SkM improved with 8 weeks of 100 mg/day of Epi treatment (14).…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, the EQ-VAS is aimed at obtaining the general health state of the participant, providing important and complementary information about the opinions of the patients regarding their own health. In a trial conducted in older individuals, an improvement in QoL measured with the EQ-5D was observed in the group that received a natural beverage made of flavonoid-rich cocoa powder, with a significant decrease in their perception toward problems in mobility and pain/discomfort, and without changes in the rest of the dimensions [ 33 ]. In our study, the proportion of women in each of the categories of the dimensions analysed in the EQ-5D-3L remained similar after the intervention.…”
Section: Discussionmentioning
confidence: 99%